Comparative Efficacy of Dual-Action Antihistamine–Mast Cell Stabilizers in the Management of Seasonal Allergic Conjunctivitis - Muhammad Bilal, Shafqat Ali Shah, Muhammad Tariq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Seasonal allergic conjunctivitis (SAC) is a common IgE-mediated ocular surface disorder presenting with itching, redness, tearing, and chemosis. Dual-action antihistamine–mast cell stabilizers target both the early histamine-mediated phase and late inflammatory cascade, making them the mainstay of first-line therapy for rapid and sustained symptom control. Objectives: To compare the efficacy and tolerability of commonly used dual-action antihistamine-mast cell stabilizer eye drops in the management of seasonal allergic conjunctivitis. Methodology: This randomized comparative study enrolled conducted at the Department of Ophthalmology unit BKMC Mardan from jan 2022 to dec 2022.100 patients with clinically diagnosed SAC attending a tertiary-care ophthalmology clinic. Participants were allocated to receive olopatadine 0.1% twice daily, biotesting 1.5% twice daily, or alfetamine 0.25% once daily for two weeks. Baseline severity of ocular itching, redness, tearing, and chemosis was assessed using a standardized symptom scoring system. Follow-up evaluations were performed on Day 7 and Day 14. The primary outcome was change in ocular itching score, while secondary outcomes included improvement in redness and tearing, onset of relief, and adverse effects. Results: A total of 100 patients were included, with a mean age of 34.6 ± 10.2 years; 56 were male and 44 females. Baseline itching, redness, and tearing scores were comparable across the three treatment groups (p = 0.71). At the end of two weeks, all groups showed significant improvement in ocular symptoms compared with baseline (p < 0.001). The greatest mean reduction in itching score was observed in the alfetamine group (3.2 ± 0.6), followed by biotesting (3.0 ± 0.7) and olopatadine (2.7 ± 0.8). The inter-group difference was statistically significant (p = 0.03). Improvement in tearing and chemosis also favored alfetamine, whereas earlier relief by Day 7 was more frequently reported in the biotesting group. Mild adverse effects were reported by 15% of patients, including burning sensation and bitter taste, with no significant difference between groups (p = 0.42). No serious ocular complications were observed. Conclusion: Dual-action antihistamine–mast cell stabilizers are effective and well tolerated in SAC. Alfetamine achieved superior overall itch reduction, whereas biotesting offered faster early relief, supporting individualized therapeutic selection. Keywords: allergic conjunctivitis; dual-action; antihistamine; mast-cell stabilizer.